Infection control knowledge, beliefs and behaviours amongst cystic fibrosis patients with epidemic Pseudomonas aeruginosa. Issue 1 (December 2015) - Somayaji, R.; Waddell, B.; Workentine, M.; Surette, M.; Brager, N.; Rabin, H.; Parkins, M.
Abstract Background EpidemicP. aeruginosa (ePA) infections are common in cystic fibrosis (CF) and have been associated with accelerated clinical decline. Factors associated with ePA are unclear, and evidence based infection control interventions are lacking. Methods We prospectively collect all bacterial pathogens from adult CF patients. We performed PA strain typing on retrospectively collected enrolment samples and recent isolates to identify patients infected with ePA. All patients attending our clinic were approached to complete a survey on infection control knowledge, beliefs and exposures. We analyzed responses of those with ePA relative to the entire cohort without ePA as well as those infected with unique strains ofP. aeruginosa to assess for risk factors for ePA and differences in infection control knowledge, beliefs or behaviours. Results Of 144 participants, 30 patients had ePA (two Liverpool epidemic strain, 28 Prairie epidemic strain), 83 % of which had established infection prior to transition to the adult clinic. Risk of concomitant infecting pathogens was no different between groups although, Staphylococcus aureus and non-tuberculous mycobacteria were less common in those with ePA. Patients with ePA were more likely to have attended CF-camp and have a history of CF fundraising. Patients with ePA did not differ with respect to beliefs regarding pathogens or transmission risk, except they believed indirect contact posed little risk. Furthermore, patients with ePA were more likely to continue to associate with others with CF despite extensive counselling. Use of peer-peer online networking was minimal in both groups. Conclusion Infections with ePA are closely linked to past exposures, now routinely discouraged. As socialization is the greatest risk factor for ePA, infection control strategies for ePA must focus on discouraging face-to-face interactions amongst CF patients. As peer support remains a desire amongst patients, investment in technologies and strategies that enable indirect communication and support are required.